ANALYSIS OF THE IMPACT OF CORPORATE REPUTATION ASSESSMENT IN THE 2024 CORPORATE IMAGE AWARDS ON CORPORATE PERFORMANCE - Azzam, Abdullah (Program Studi Manajemen Keuangan Syariah, 2025)
This study aims to examine whether there are differences in financial performance between companies with high and low reputations based on the results of the 2024 Corporate Image Index (CII). This study uses five financial performance indicators: Return on Assets (ROA), Return on Equity (ROE), Net Profit Margin (NPM), Debt to Asset Ratio (DAR), and Debt to Equity Ratio (DER). The sample consisted of 78 companies, grouped into two groups based on the highest and lowest scores on the 2024 CII. The analysis method used was an independent samples t-test. The results show that although companies with high reputations have better average financial performance, the difference is not statistically significant. This indicates that a company's external reputation, as measured by the CII award, does not directly reflect its financial performance. This study provides a theoretical contribution by broadening the understanding of the relationship between reputation and financial performance and suggests the need for a multidimensional approach to evaluating corporate success.